Strategies to Minimise the Impact of COVID-19 on the Construction Industry: A Case Study of Construction Site Clusters in Malaysia - Farah Salwati Ibrahim; Muneera Esa; Ernawati Mustafa Kamal (Construction Economics and Building, 2022)
Malaysia has seen the third wave of infection since the start of the global COVID-19 pandemic, with approximately 103 construction sites involving over 14,667 workers reported from April 2020 to February 2021. This has led to limited progress in construction projects or a complete halt, resulting in late project delivery. The purpose of this paper is to investigate the factors influencing the spread of COVID-19 and the strategies taken by the affected construction sites to mitigate the spread of the outbreak. The researchers adopted a case study approach with a multiple-case design and discusses the use of an in-depth interviewing method to collect rich data on the studied phenomenon. Data were collected from three construction sites. The sites were mixed development projects in nature and provided in-depth, rigorous, and robust information. Based on the results, two categories of factors influencing the spread of COVID-19 were established. These are primary and secondary factors, such as workers’ mobilisation, uncontrolled movement of workers, and the limited practice of social distancing. Furthermore, evidence suggests that the strategies adopted to control the effects of the pandemic were a combination of government enforcement and initiatives taken by construction companies. This paper concludes that an early identification of the causes of the spread will enable appropriate implementation strategies to control the outbreak. This study is an attempt to present the experiences of one developing country as an example of a means of dealing with unexpected pandemics or other intractable diseases that can affect project delivery.